Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1139/h11-099
|View full text |Cite
|
Sign up to set email alerts
|

Wheel running prevents the accumulation of monounsaturated fatty acids in the liver of ovariectomized mice by attenuating changes in SCD-1 content

Abstract: Decreases in female sex steroids enhance the accumulation of visceral fat mass, leading to a predisposition to developing metabolic diseases. The purpose of this study was to determine whether loss of ovarian function alters the amount and (or) the fatty acid (FA) composition of triacylglycerol (TAG) levels in the liver of ovary-intact (SHAM) or ovariectomized (OVX) mice. We also sought to determine whether voluntary wheel running could attenuate the associated changes in the liver. Twenty-two C57/BL6 female m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 73 publications
6
37
0
Order By: Relevance
“…Isolation of RNA and subsequent cDNA synthesis from the gastrocnemius or plantaris muscles and mouse testes (positive control) was performed according to the previously described techniques ( 15,16 ). Specifi c primers for mouse Brca1 were as follows: forward 5 ′ -CAC AGC GTA TGC CAG AGA AA-3 ′ and reverse 5 ′ -ATC CTG GGA GTT TGC ATT TG-3 ′ .…”
Section: Mouse Mrna Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Isolation of RNA and subsequent cDNA synthesis from the gastrocnemius or plantaris muscles and mouse testes (positive control) was performed according to the previously described techniques ( 15,16 ). Specifi c primers for mouse Brca1 were as follows: forward 5 ′ -CAC AGC GTA TGC CAG AGA AA-3 ′ and reverse 5 ′ -ATC CTG GGA GTT TGC ATT TG-3 ′ .…”
Section: Mouse Mrna Analysismentioning
confidence: 99%
“…Mouse skeletal muscle was mechanically homogenized according to previously described techniques ( 15,19 ). Human skeletal muscle biopsies were homogenized on ice using glass-on-glass homogenizers in RIPA buffer [150 mM NaCl, 10 mM Tris-HCl, 5 mM EDTA, 0.5% Na deoxycholate, 0.1% SDS, 1% Triton X-100, and protein inhibitor cocktail complete mini (Roche Diagnostics)].…”
Section: Homogenizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise stimulates glucose uptake by skeletal muscle from the blood (Goldstein et al 1953), decreases fat content from the adipose tissue (Gollisch et al 2009), and prevents fat accumulation in the liver (Jackson et al 2011). Besides the effects of exercise on peripheral tissues, voluntary exercise also improves brain function.…”
Section: Introductionmentioning
confidence: 99%
“…While low aerobic fitness is a powerful independent risk factor for all-cause mortality and metabolic disease risk (24), the impact of aerobic fitness on postmenopausal metabolic function per se is largely unknown. Animal studies have demonstrated that loss of ovarian hormones causes a reduction in physical activity and that exercise can offset these effects (18), but no studies have investigated the unique role played by intrinsic aerobic fitness, independent of exercise, on the changes in energy balance, body composition, and insulin resistance following ovariectomy (OVX). Accordingly, the purpose of the present study was to test the hypothesis that high intrinsic aerobic fitness protects against the metabolic dysfunction associated with OVX in rats.…”
mentioning
confidence: 99%